Compact plasma and focused ion beams - Bhattacharjee, Sudeep (Taylor & Francis, 2014)
This book discusses a method to produce a compact microwave plasma by overcoming challenges posed both by (i) geometrical cutoff of the waveguide and (ii) density cutoff of the plasma. It then presents the properties of such compact plasmas. Finally, it brings out a new area of applications where such compact high densities plasmas are utilized for multi-element focused ion beams.